Environmental sustainability: Carbon emission reduction strategies and reporting among Malaysian construction companies - Ghazali, Z. (Institute of Electrical and Electronics Engineers Inc., 2015)
Firm's response to environmental sustainability has increasingly become important to business research and practices over the past decades. The rapid depletion of natural resources, climate change, and concentration on greenhouse gas emissions grabbed much of the attention of regulators, researchers, academia and practitioners around the world. This paper focuses on Malaysian construction sector which has low status of CO2 emissions as evidenced in a sample of 32 companies from 2011 to 2013. The content analysis procedure of the annual reports for the sample companies revealed that most of the companies are committed towards environmental sustainability but only few disclose their efforts for CO2 emissions. Moreover, most of their disclosures are superficial and repetitive in nature for the sake of reporting only which have no practical value. Thus, this paper strongly recommends the implementation of effective strategies and taking further practical steps to mitigate CO2 emissions in the Malaysian sector. The paper has implications for researchers, academia, regulatory bodies and practitioners. The paper also fills the exhibited gap in literature. Â© 2015 IEEE.